Mengulik Euforia Amnesti Pajak: Hukum-APBN-Utang-Pajak (Studi Kasus Kantor Pelayanan Pajak Pratama Kabupaten X) - Whedy Prasetyo (Universitas Trunojoyo Madura, 2018)
This study aims to investigate Law. 11 of 2016 on Tax Amnesty dated July 1, 2016 which aims to increase tax revenues and encourage the transfer of assets abroad to the country (asset repatriation). A case study on Tax Office Primary Regency Xwith a qualitative approach is used in this study by showing the response of the presence of PSAK 70 on the Implementation of Asset Accounting (Treasures) and Liabilities (Debt) Tax Amnesty in a proportional perspective. The result is the growth of tax compliance in the motivation and mental attitude of the taxpayer through integrity, responsibility, discipline, accuracy, cooperation, honesty, visi onary, motivation and attitude to achieve tax functions as Budgeter, Regulern, Democracy, and Redistribution in tax amnesty. These four functions are a manifestation of the Law-APBN-Debt-Taxon tax realization targets, therefore tax is expected to be a form of public awareness (voluntary compliance) in contributingto the State through self assessment. Finally, the function of tax amnesty can be an economic tool for the welfare of the people, one of the sources of development financing, to encourage economic growth through the current development policy and it means to create job opportunities and other economic and business opportunities. So that the two parties between the government and WP have a synergistic relationship in recording and reporting the amount of taxes that become obligations, toward a fair tax revenue structure.